2015
DOI: 10.1073/pnas.1422187112
|View full text |Cite
|
Sign up to set email alerts
|

The histone methyltransferase SETDB1 represses endogenous and exogenous retroviruses in B lymphocytes

Abstract: Genome stability relies on epigenetic mechanisms that enforce repression of endogenous retroviruses (ERVs). Current evidence suggests that distinct chromatin-based mechanisms repress ERVs in cells of embryonic origin (histone methylation dominant) vs. more differentiated cells (DNA methylation dominant). However, the latter aspect of this model has not been tested. Remarkably, and in contrast to the prevailing model, we find that repressive histone methylation catalyzed by the enzyme SETDB1 is critical for sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
81
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 35 publications
5
81
0
Order By: Relevance
“…2,24 Setdb1 was recently shown to contribute to the silencing of ERVs in B lymphocytes; however, the transcriptional activation of ERVs was dependent on the regulatory architecture of their long terminal repeats and the availability of corresponding B-cell-specific transcription factors such as Pax5. 25 In the present study, we found that H3K9me3 and DNA methylation were not largely altered at ERV loci and derepression of ERVs was minimal in the absence of Setdb1. These results confirm previous findings obtained in neural progenitor cells and fibroblasts 2,24 and highlight the important role of DNA methylation in the silencing of ERVs in HSPCs.…”
Section: Discussionsupporting
confidence: 48%
“…2,24 Setdb1 was recently shown to contribute to the silencing of ERVs in B lymphocytes; however, the transcriptional activation of ERVs was dependent on the regulatory architecture of their long terminal repeats and the availability of corresponding B-cell-specific transcription factors such as Pax5. 25 In the present study, we found that H3K9me3 and DNA methylation were not largely altered at ERV loci and derepression of ERVs was minimal in the absence of Setdb1. These results confirm previous findings obtained in neural progenitor cells and fibroblasts 2,24 and highlight the important role of DNA methylation in the silencing of ERVs in HSPCs.…”
Section: Discussionsupporting
confidence: 48%
“…7G), which is in full agreement with a recent study of Setdb1 function in B cells (Collins et al, 2015). In wild-type cells, Setdb1 binds to MLV retrotransposons and establishes a repressive chromatin structure that prevents access of activating transcription factors.…”
Section: Discussionsupporting
confidence: 90%
“…There is emerging evidence that transposable elements contain transcription factor binding sites (Xie et al, 2010) and may even physiologically act as tissue-specific enhancers (Xie et al, 2013). A recent study showed that the master B cell transcription factor Pax5 may mediate forced expression of the same MLV elements that we found to be upregulated in Setdb1-deficient pro-B cells (Collins et al, 2015) (Table S3). However, additional cell type-specific transcription factors are likely to contribute to MLV transcription, as Setdb1-deficient mouse embryonic fibroblasts (Matsui et al, 2010) or myeloid cells (data not shown), which do not express Pax5, also display derepression of MLV retrotransposons.…”
Section: Discussionmentioning
confidence: 64%
“…Second, in mature T lymphocytes, a significant fraction of TEs bound by KAP1 in human ESCs still carries the co-repressor . Third, KAP1 deletion in neuronal progenitors activates some endogenous retroelements (Fasching et al, 2015), and selected ERVs are similarly induced in murine B lymphocytes or mouse embryonic fibroblasts (MEFs) depleted for SETDB1 (Collins et al, 2015;Wolf et al, 2015b). Correspondingly, human KRAB-ZFPs display extensive and cell-specific patterns of expression in all adult tissues examined Liu et al, 2014).…”
Section: Heterochromatin Induction In Early Development and Te Controlmentioning
confidence: 99%